Determinants of Internal Audit Effectiveness and Implication on Corruption Prevention in The Religious Ministry - Ika Shohihah; Ali Djamhuri; Lilik Purwanti (Sekolah Pascasarjana Universitas Brawijaya, 2018)
This study aims to examine and analyze the influence of auditor competence, independence of internal audit organization, relationship between internal and external auditors, management support to the effectiveness of internal audit, and the effect of internal audit effectiveness on the corruption in Inspectorate General of Ministry of Religious Affairs RI involving 152 respondents. The analysis method employed PLS (Partial Least Square) by utilizing SmartPLS 2.0 software. The result of the research shows that there is positive influence of the auditor competence, independence of internal audit organization, relationship between the internal and external auditors, and management support to the effectiveness of internal audit. This study proves that the effectiveness of internal audit tends to decrease corruption. In addition, this study also supports the Inspectorate General of Ministry of Religious Affairs as part of the governance of Kemenag organizations can help fight corruption.